(3EbdjO GdfLGM aj TQM OYGA GdUHGMs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg NGdb GdeNdhbGJ heHJOYgG hUGfY GdeUfhYGJ heNJQYgG GdPj YLR Yf JYHjQ LdGdg (B... (3ebOeI bO GTJgQ fSHI gPG GdOYGA GdeYQha HOYGA GdUHGM Edi EeGeefG CejQ GdeDefjfs
(3BNQgG (B:s
(3BNQgG(B: (3haj GdMOjK dG Mhd hdG bhI EdG HGddg cfR ef cfRh GdLfI, eYfi chfgG cfRG ef cfhR GdLfI Gj jYO dbGFdg hjONQ dg ef GdKhGH eG jbY dg HGdLfI ehbY GdcfRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs